Your brain on Latino comics : from Gus Arriola to Los Bros Hernandez - Aldama, Frederick Luis, 1969- (Cognitive approaches to literature and culture series., 2009)
Though the field of comic book studies has burgeoned in recent years, Latino characters and creators have received little attention. Putting the spotlight on this vibrant segment, Your Brain on Latino Comics illuminates the world of superheroes Firebird, Vibe, and the new Blue Beetle while also examining the effects on readers who are challenged to envision such worlds. Exploring mainstream companies such as Marvel and DC as well as rising stars from other segments of the industry, Frederick Aldama provides a new reading of race, ethnicity, and the relatively new storytelling medium of comics themselves. Overview chapters cover the evolution of Latino influences in comics, innovations, and representations of women, demonstrating Latino transcendence of many mainstream techniques. The author then probes the rich and complex ways in which such artists affect the cognitive and emotional responses of readers as they imagine past, present, and future worlds. Twenty-one interviews with Latino comic book and comic strip authors and artists, including Laura Molina, Frank Espinosa, and Rafael Navarro, complete the study, yielding captivating commentary on the current state of the trade, cultural perceptions, and the intentions of creative individuals who shape their readers in powerful ways.